Plasma Biochemical Profile Of Murrah Buffaloes (Bubalus bubalis) Fed Peripartum Positive Dietary Cation Anion Difference Diet - Arora, A.; Singh, P.; Dhindsa, S. S.; Grewal, R.S.; Singh, N.; Honparkhe, M.; Malik, V. S. (The Indian Journal of Animal Reproduction, 2021)
A comparative study was done to evaluate peripartum Dietary Cation-Anion  Difference (DCAD) feeding in buffaloes. Murrah buffaloes (n=25) were randomly  divided into three groups: Group 1 (n=10), Group 2 (n=10) and Group 3 (n=5,  control). Buffaloes in Group 1 and Group 2 were fed DCAD levels of -100 mEq 100  g-1 of dry matter (DM) starting 30 days prepartum. During the postpartum period  and upto 30 days, Group 1 was fed on DCAD levels of +300 mEq 100 g-1 and Group  2 was fed DCAD levels of +400 mEq 100 g-1. Group 3 (control) buffaloes were fed  standard diet without any cationic or anionic salts. Blood sampling was carried out  on day -7, 0, 20, 26, 32, 38, 45, 52 and 54 of calving. Plasma urea nitrogen (PUN) in  Group 1, 2 and 3 buffaloes ranged from 16.5±0.88 to 18.3±0.68 mg dl-1, 16.0±0.40  to 17.8±0.47 mg dl-1 and 15.4±0.79 to 22.0±0.86 mg dl-1, respectively. PUN after 26  days postpartum was significantly low (P< 0.05) in buffaloes fed on two different  DCAD levels than the control group. Creatine Kinase (CK) activity in Group 1,  2 and 3 buffaloes ranged from 175.22±15.4 to 241.44±21.9 UL-1, 192± 23.26 to  575.75±162.05 UL-1 and 187.6±92.75 to 319±50.06 UL-1, respectively. In Group 2,  CK activity was significantly higher (P< 0.05) as compared to group 1 and group 3  across 38 and 54days postpartum. Creatinine in Group 1, 2 and 3 buffaloes ranged  from 1.56±0.12 to 2.21±0.14 mg dl-1, 1.70±0.08 to 2.58±0.23 mgdl-1 and 1.84±0.17 to  2.22±0.29 mg dl-1, respectively. In Group 3, creatinine was significantly higher (P
Keywords: Dietary Cation Anion Difference; Plasma Urea Nitrogen; Creatine Kinase; Creatinine; Glucose; Total Protein; Buffaloes